DINAMIKA TUNTUTAN BSELIS SAAT PERKAWINAN DAN DAMPAK HUKUM NYA DALAM MASYARAKAT DI DUSUN OENOH DESA OEBAFOK KECAMATAN ROTE BARAT DAYA KABUPATEN ROTE NDAO - Ndun, Yoran Viktor; Hedewata, Agustinus; Aloysius, Sukardan (Petitum Law Journal, 2023)
The dynamics of belis demands during marriage in the community in Oen oh Hamlet. Oebafok Village, Rote Ndao Sub-district, that is, that in ancient times if the belis did not comply with the agreement then the marriage or marriage was annulled. If it is completed according to the agreement of the two extended families or the two families who will carry out the marriage, the marriage will take place. But in this day and age there began to be a world of education, and slowly the community has begun to understand and no longer want to burden their children, so there are no longer demands when something is not in accordance with the agreement then there is only a discussion between the two families concerned. So there are no more fines or dynamics on belis demands that often occur. This research is an empirical legal research method with direct data collection techniques at the research site and conducting interviews with four respondents. The data were analyzed in a qualitative descriptive manner.The results of this study show that: (1) In ancient times if the belis was not in accordance with the agreement then the marriage was annulled. If it is completed according to the agreement of the two extended families, the marriage takes place. (2) If you do not meet the belis, you will be subject to a fine in the form of Mai, which means that one Mai has a nominal value of five million, but it can be one Mai valued at two million hundred or it can also go down based on the results of discussions between the two families.